Solution Blowing of Palygorskite-Based Nanofibers for Methylene Blue Adsorption - LIU Chang; MA Youwei; GUO Ying; WANG Xueming; SHI Lei; LI Lei; ZHUANG Xupin (东华大学学报（英文版）, 2022)
TS171; Palygorskite ( PG) adsorbent with superior adsorption property and ion-exchange ability is highly desired in the field of dye removal. However, it generates high amounts of precipitation due to the granular form, resulting in secondary pollution after adsorption. Herein, the novel high porosity PG-based nanofibers that are easy for operating and retrieving have been fabricated using effective solution blowing and subsequent calcination. The obtained highly efficient adsorption nanofibers exhibit large specific surface area about 170.50 m2/g with average diameter from 243 nm to 365 nm. Based on the abovementioned nanofibrous structure and negatively charged PG, the solution blowing of PG-based nanofibers (SBPNs) showed high adsorption capacity for methylene blue (MB) (112.36 mg/g). In addition, the adsorption of SBPNs is well described by the Langmuir isotherm model. This work provides new SBPNs forming process for the fields of dye removal, which may achieve the production of PG adsorbents at the industrial level.